DAMPAK PELAKSANAAN CORPORATE SOCIAL RESPONSIBILITY (CSR) BANYAN TREE RESORT DALAM MENDUKUNG KONSEP SUSTAINABLE TOURISM DEVELOPMENT DI DESA UNGASAN BALI - Manik, Molinda Hotmauly Br (2014)
The increase in tourist visits to the island of Bali in fear will bring adverse effects such as damage to the environment, so most of the people are still there who have negative thoughts towards the development of tourism today. They thought that would damage the environment and tourism bring harm to their culture that they have been held so far. The impact would also tend to undermine the sustainability of the future. In overcoming such negative things mentioned above, today some companies have a department that is responsible for carrying out an activity or social obligations that we know as the company's Corporate Social Responsibility (CSR). This study will examine the impact of CSR on the village sustainability Ungasan Bali. The method used in this research is descriptive quantitative method. There are two variables in the study of CSR and Sustainable Tourism Development. The analysis used in this study is the analysis of t-test with paired sample method. Respondents in this study are the communities Kelod Banjar Bali Ungasan village 90 respondents. Based on the research results, the public response to the corporate social responsibility program that is implemented by Banyan Tree Ungasan Ungasan Village Resort in Bali is very good and gave benefit to society. Sustainable Tourism Development in the village of Ungasan, Bali prior to the implementation of corporate social responsibility program Banyan Tree Ungasan Resort or before 2010 according to public response and after 2010 until now has increase. This study shows that there are significant differences or changes or real before and after the implementation of corporate social responsibility program Banyan Tree Ungasan Resort.